DISTRIBUTIVE CHANGE OF TYPICAL ECOSYSTEMS IN THE QUANG NINH COASTAL AREA - Thao, Nguyen Van; Bao, Dang Van; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2014)
In this reseach, the remote sensing data combined to field survey data and existing results of reseaches were used to evaluate and analyse distribition change of the typical ecosystems in the Quang Ninh coastal area such as mangrove forest, tidal flat, coral reef and seagrass bed. During the 20 last years, these ecosystems have been reduced largely in the distributive area. About 7,253ha (25.2%) of  mangrove area and 10,425ha (21.5%) of tidal flat area were destroyed from 1990 - 2008. Without good and very good categories, the coral reefs in the Ha Long bay has lost over 30% number of speices, 20.5% number of genus and 70% of area. In the Co To Archipelago, the coral reefs were largely degraded on number of species (over 80%) and distributive area (over 90%) from 2000 - 2007 period. The seagrass ecosystem has been reduced, over 80% of distribution area, too. The seagrass was discovered before in some sites such as Dam Buon, Ha Coi and Dam Ha bay, but disappeared in 2009. The activities of aquaculture farm, ground filling and fishing by poison; and typhoons and floods are main causes to reduce the distributive area of these typical ecosystems.